INITIATING AN INVESTIGATION FOR CRIME OF MURDER - Georgieva, Nataša (Journal of process management and new technologies, 2020)
In the paper below, are shown the principles that are intended to present the procedure for initiating an investigation into the crime of murder. Through these principles, detectives and chief investigators at the crime scene are able to thoroughly verify and exaggerate all facts that can be, or that are relevant to the investigation. The first information is usually transmitted to detectives or investigators through police stations. The paper further explains the procedures that follow upon arrival at the place where the body was found. Then, the time of arrival, the exact address of the location, the persons present, body condition and position, cause of death information, weather conditions, lighting if night, as well as places of arrival are noted, and fully observation is made in manner of location of possible eyewitnesses or persons who could see what happened, possible location of video surveillance, such as bank cameras, super markets, parking lots, etc. Among the duties of a detective upon arriving at the scene include an initial interview with the responsible police officer, interviewing medical personnel, dealing with curiosity observers and eyewitnesses at the crime scene. Following this stage, the search follows as an important research tool. In the case of murder with rape, a thorough initial medical examination is performed at the scene. The chief investigator and the detective in charge of the murder investigation have complete control of the scene. The alleged detective and the murder investigator face a complex problem, so they need to consider motives, manner of execution, and various physical evidence. From here, teamwork is crucial to the success of the investigation.